Deep Brain Stimulation of the Nucleus Accumbens Core Affects Trait Impulsivity in a Baseline-Dependent Manner - Schippers, Maria C.; Bruinsma, Bastiaan; Gaastra, Mathijs; Mesman, Tanja I.; Denys, Damiaan; De Vries, Taco J.; Pattij, Tommy (Frontiers in Behavioral Neuroscience, 2017)
Deep brain stimulation (DBS) of the nucleus accumbens (NA) is explored as a treatment for refractory psychiatric disorders, such as obsessive-compulsive disorder (OCD), depressive disorder (MDD) and substance use disorder (SUD). A common feature of some of these disorders is pathological impulsivity. Here, the effects of NAcore DBS on impulsive choice and impulsive action, two distinct forms of impulsive behavior, were investigated in translational animal tasks, the delayed reward task (DRT) and five-choice serial reaction time task (5-CSRTT), respectively. In both tasks, the effects of NAcore DBS were negatively correlated with baseline impulsive behavior, with more pronounced effects in the 5-CSRTT. To further examine the effects of DBS on trait impulsive action, rats were screened for high (HI) and low (LI) impulsive responding in the 5-CSRTT. NAcore DBS decreased impulsive, premature responding in HI rats under conventional conditions. However, upon challenged conditions to increase impulsive responding, NAcore DBS did not alter impulsivity. These results strongly suggest a baseline-dependent effect of DBS on impulsivity, which is in line with clinical observations.